## raebaby420 2 years ago Use the substitution method to solve the following system of equations. x + 2y – z = 7 4x – y + 3z = –2 2x + 2y – z = 9

1. Zelda

Well, here we go: First let's set the first equation equal to: – z = 7 - x - 2y Which becomes: z = x+2y - 7 okay?

2. raebaby420

Yes

3. Zelda

No put this in equation #2: 4x – y + 3z = –2 Becomes: 4x – y + 3(x+2y - 7) = –2 Which becomes: 4x - y +3x +2y -21 = -2

4. Zelda

With me so far?

5. raebaby420

Yes kinda

6. Zelda

So, then we combine like terms to get: 4x - y +3x +2y -21 = -2 7x + y -21 = -2 y = -7x +19 And finally put this in the third equation and solve for x. So put in the first and second equations into the third one and solve for x.

7. raebaby420

Im not sure

8. Zelda

So we have z = x+2y - 7 and we have y = -7x +19 SO in the third equation: 2x + 2y – z = 9 Wherver you see a z, put that equation, and where you see a y, put in the equation for y. (First put in the y in the z equation)

9. raebaby420

I got it! thanks!!

10. Zelda

No problem kiddo.